ON METHODICAL ISSUES OF PROBLEM FORMULATION AND HYPOTHESIS ADVANCEMENT OF DISSERTATIONAL RESEARCH IN THE SPHERE OF PSYCHOLOGY - Khudoyan, S.; Grigoryan, G. (Main Issues Of Pedagogy And Psychology, 2013)
The issues concerning the concrete definition and formulation of the problem and advancement of the hypothesis of dissertational research are analyzed in the article. The basic types of hypothesis, the ways of creation of hypothesis, the basic mistakes the candidates make for a degree advancing the hypothesis in dissertational researches on psychology, are submitted.